Dobre praktyki w zarządzaniu personelem stosowane w przedsiębiorstwach społecznie odpowiedzialnych - Brzozowski, Tomasz (Good Practices in Staff Management Used by Social Responsible Companies, 2008)
One of the key elements of corporate social responsibility is creating a profitable relation with employees. The most popular activities in this area are employees engagement as volunteers, incorporating employees in management processes, equal chances assurance for all employees and internal communication improvement. These practices were described usually in corporate social reports and marked out by Responsible Business Forum in their market research. The author of this article analyzed what kind of indicators use companies in published social reports. It seems that companies do not use a few of indicators to quantify their activities in a scope of staff management. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 523-530